Male infertility microsurgical training - Mehta, Akanksha; Li, Philip S.; Goldstein, Marc (Translational Andrology and Urology, 2014)
A strong foundation in microsurgical techniques is imperative for urologists and clinical andrologists specializing in male infertility. Laboratory-based microsurgical training enhances surgical skills, improves surgeon confidence, and reduces stress and operating time, thereby benefiting both the patient and the surgeon. The laboratory environment additionally allows for the development of novel and innovative techniques. This review provides guidelines for setting up a microsurgical laboratory to develop and enhance microsurgical skills using synthetic and animal models.